Portal vein velocity and its dynamics: a potentially useful tool for detecting clinically silent transjugular intrahepatic porto-systemic shunt dysfunction using Doppler ultrasonography - Crăciun, Rareș; Ștefănescu, Horia; Nicoară-Farcău, Oana; Fischer, Petra; Fodor, Andreea; Tanţău, Marcel; Radu, Corina; Spârchez, Zeno; Procopeţ, Bogdan (Ultrasound International Open, 2024)
Background  Ultrasound (US) surveillance for transjugular intrahepatic portosystemic shunt (TIPS) dysfunction has yet to be standardized, as clear-cut criteria have not been conventionally defined. This study evaluated the role of US-based parameters in detecting hemodynamic TIPS dysfunction (HD).Methods  We included consecutive patients treated with TIPS. All patients were scheduled within the first six weeks after the procedure for TIPS revision, comprised of a Doppler US exam and invasive hemodynamic reassessment. Clinical TIPS dysfunction (CD) was defined as symptom recurrence, while HD was defined by a portal pressure gradient (PPG)≥12 mmHg. The predictive capabilities of Doppler US for predicting TIPS dysfunction were tested against the hemodynamic gold standard.Results  86 patients were included. Secondary prophylaxis of variceal bleeding was the main indication for TIPS in 72 patients (83.7%), while 27 (31.4%) had refractory ascites. HD occurred in 37 cases (43%), of which 25 patients (67.5%) had no CD. Patients with HD had a significantly lower portal vein velocity (PVV): 35 (20–45) cm/s vs. 40.5 (35–50) cm/s, p=0.02. Compared to the immediate post-TIPS assessment, the patients without HD had a ΔPVV of 6.08±19.8 cm/s vs. a decrease of − 8.2±20.2 cm/s in HD (p=0.04). Using a cut-off value of 40.5 cm/s, PVV had an AUROC of 0.705 for predicting HD, while the addition of ΔPVV (cut-off 9.5 cm/s) improved the AUROC to 0.78.Conclusion  Despite adequate symptom control, a considerable percentage of patients have a post-TIPS PPG≥12 mmHg. The dynamic assessment of PVV and its temporal dynamics can reliably predict TIPS dysfunction.
Keywords: shunts; interventional procedures; transjugular intrahepatic porto-systemic shunt; TIPS; Color Doppler ultrasound